Konflik Kejiwaan Tokoh Utama dalam Novel Retak karya Azhara Natasya - Utami, Utri; Hayati, Yenni (Persona: Kajian Bahasa dan Sastra, 2023)
The novel Retak by Azhara Natasya tells about the complexity of the life of the character Gladys which results in her mental health being seriously disturbed. Starting from his life at home where he didn't get love from his parents, his life at school where he became a victim of bullying, to his love life from a different religion. This research aims to describe: (1) the forms of psychological conflict of the main character in the novel Retak by Azhara Natasya, (2) the factors causing the psychological conflict of the main character in the novel Retak by Azhara Natasya, (3) the impact of the psychological conflict of the main character in the novel Retak The work of Azhara Natasya. The type of research is literary research using descriptive methods. The subject used in this research is the novel Retak by Azhara Natasya. Data collection techniques in this research are, (1) reading and understanding the novel, (2) literature study, (3) identifying characters in the novel, (4) marking parts of the story that contain data on the character's psychological conflict, and (5) taking an inventory of the data. into inventory format. There are four data analysis techniques in this research, namely (1) identifying and classifying data, (2) analyzing data, (3) interpreting data, (3) drawing conclusions. The research results obtained are forms of inner conflict of the main character in the novel Retak by Azhara Natasya which are divided into depression, anxiety, feelings of anger, frustration, feelings of insecurity, fear, feelings of inadequacy, heartache. The factors that cause the main character's psychological conflict are divided into the unfulfillment of basic human needs, namely physiological needs, security needs, love and belonging needs, self-esteem, and self-actualization. The impact of the character's psychological conflict is divided into feelings of guilt, self-punishment, and sadness.